Diagnóstico de la planta de tratamiento de lixiviados del relleno sanitario Colomba El Guabal (2018)
The Colomba El Guabal landfill is located at Yotoco, Valle del Cauca and currently receives an average of 2260 Mg/d of solid waste from 10 municipalities of Valle del Cauca department and 4 municipalities of Cauca department. The leachates generated by the disposal of these wastes are handled through an existing Treatment Plant at the landfill. This article presents the Colomba El Guabal landfill leachate treatment plant diagnostic, as from monitoring carried out at the treatment units and the evaluation of the operational parameters (Castañeda S., 2018). The analysis found that physicochemical treatment units require optimization processes based on detailed coagulant dosing studies, optimal coagulation conditions and required aids. Under the current operating conditions, the effluent does not satisfice the quality limits for chlorides and arsenic.